Does serum Gas6 level change in active uveitis? - Ozgur Cakici; Omer Faruk Yilmaz (Therapeutic Advances in Ophthalmology)
Purpose: The aim of this study was to investigate serum Growth Arrest-Specific Protein 6 (Gas6) levels in the active and inactive periods of uveitis. Material and methods: In this study, serum Gas6 levels were evaluated in 21 patients during active and inactive periods. After measuring serum Gas6 levels in the active phase, the serum Gas6 test was repeated in the inactive period. Commercial Enzyme-Linked Immunosorbent Assay (ELISA) kits (Gas6, WKEA Med Supplies Corporation, NY, USA) were used to measure Gas6 levels. Plasma concentrations were analyzed with an ELISA reader at 450 nm following the manufacturer’s instructions. Results: In the study, the mean age of 21 patients was 33 (7–62) years. The mean follow-up period was 30.05 ± 18.76 months. While the average Gas6 value measured during active uveitis attacks was 1.02 ± 0.39 ng/mL (range: 0.54–2.12), the Gas6 value during the passive period was 0.71 ± 0.23 ng/mL (range: 0.39–1.17). The Gas6 level during active uveitis attacks was significantly higher than during the passive period ( p  = 0.04). Conclusion: The findings of this study suggest a notable elevation in serum Gas6 levels across all cases of active uveitis, irrespective of the underlying etiology, whether infectious or noninfectious. To successfully integrate serum Gas6 levels into the diagnostic and follow-up protocols for active uveitis, additional comprehensive investigations are imperative.